A Case Series of Spp. Bacteremia in the Pediatric Population - Lim Ming Chiang MPharm Clin; Sim Cian Yi BPharm (Hons); Everlyn Coxin Siew MPaeds; Syarida binti Badrulzaman MPaeds; Siti Iryawani binti Rahman MRCPCH (SAGE Publishing, 2023)
Elizabethkingia species are multi-drug resistant, Gram-negative bacteria that can adapt to different environmental conditions and rarely cause infections in humans but can be fatal among immunocompromised populations. We report our first experience of managing 2 pediatric patients infected with Elizabethkingia species. Over 12-months, 2 pediatric patients were infected with Elizabethkingia species in our hospital. They were both immunocompromised and were initially covered with broad spectrum antibiotics. Their conditions deteriorated and further investigations revealed the growth of Elizabethkingia species from the blood culture. Change of antibiotics was commenced and marked improvement was shown along the course of treatment. Both eventually completed the treatments and recovered remarkably well with no complications from the infections. However, colonization of the Elizabethkingia species was not identified on our environmental surveillance. Timely and appropriate anti-infectives and supportive management have shown marked improvement and disease curability in our patients who suffered from bacteremia and multiple liver abscesses.